Unsettling utopia the making and unmaking of French India - Namakkal, Jessica (Columbia studies in international and global history., 2021)
"Unsettling Utopia looks to French India, five territories held by the French scattered throughout the South Asian subcontinent, to explore the connections between colonialism, settlement, border-making, decolonization, citizenship, and utopian place-making. Historian Jessica Namakkal begins with the early days of colonization in French Pondicherry, "The Paris of India," and traces the unusual tensions between European colonial powers looking to remake India in their own image. Later, she explores how after formal decolonization took hold across the subcontinent, Western-led ashrams and utopian communities that remained--most notably the Sri Aurobindo community near Pondicherry--came to exercise a form of de-facto colonization that lasts to the present day. Drawing on a mix of original archival research and contemporary ethnography, this book uniquely repositions an understudied colonial encounter to shed new light on the legacies of colonialism"--